Upaya Meningkatkan Hasil Belajar PKn Menggunakan Strategi Pembelajaran Round Table pada Siswa Kelas V SD Negeri 09 Koto Tinggi Kecamatan Gunuang Omeh - Asni, Asni (Jurusan PIPS FKIP UMMY Solok, 2018)
This research is a classroom action research using a qualitative approach. This research was carried out on fifth grade students of SD N 09 Koto tinggi in Gunuang Omeh District, which total number is eleven students. The instrument used to collect data in the form of observation sheets, documentation and test of learning outcomes. The data obtained in the study were analyzed using qualitative and quantitative data analysis. This research was conducted in two cycles and each cycle consisted of two meetings. The research results from each cycle of Civics learning that have been implemented using Round Table Learning Strategies in class V SD N 09 Koto Tinggi Gunuang Omeh District shows an increase in both the learning process and student learning outcomes. This can be seen from the achievement of students in learning, where in the first cycle of meeting 1 the percentage of completeness was reached 18.18% with an average score of 66.97 students, in the first cycle of meeting 2 the percentage of completeness is 54.44% with the average 72.27 students. Whereas in the second cycle showed a fairly high increase that reached 100% completeness percentage with the average value of students in the second cycle of meeting 1 was 86.06 and in cycle II meeting 2 was 92.27. Thus it can be concluded that the use of the Round Table Learning Strategy can improve student learning outcomes in Civics learning in class V SD N 09 Koto Tinggi Gunuang Omeh District, Lima Puluh Kota District.